Benzopyrene And moisture content In Wood Fish (Katsuobushi) Processed Using Conventional Smoking And Oven - Epsilon B. S Zagoto; Hanny W. Mewengkang; Eunike L. Mongi; Roike I. Montolalu; Silvana D. Harikedua; Feny Mentang (Sam Ratulangi University, 2022)
Wooden fish is one type of processed fish product that has undergone a series of processes such as boiling and multilevel smoking until the texture becomes as hard as wood and dark brown-black in color. Usually, wooden fish uses skipjack tuna, but wood fish which is treated with smoke causes high levels of benzoic acid. a) pyrene in wood fish meat is high. The sample selection was taken as many as 2 pieces of wooden fish products, the samples taken would be shaved and then blended and the prepared samples would be tested including analysis of benzo(a)pyrene content and water content. The test method for benzo(a)pyrene uses HPLC and water content testing, using the Moisture Determination Balance FD-660, Analysis of benzo(a)pyrene levels and water content taken from the data of the last 4 years, trend data in research that has been carried out on levels of benzo(a) pyrene and water content, in the electric oven the highest content of benzo(a)pyrene in 2022 is 4.52 ppb and the highest water content in 2021 is 23.50% while conventional smoking has the highest benzo(a)pyrene content in 2019 of 56.6 ppb and the highest water content in 2020 by 19.40%. Testing the water content analysis of the moisture content in the oven is 22.50% and conventional smoking.is 19.40% Keywords: Wood Fish, Benzo(a)pyrene, Moisture Content, Smoking, Oven Abstrak Ikan kayu adalah salah satu jenis produk olahan ikan yang telah mengalami rangkaian proses seperti perebusan dan pengasapan bertingkat, hingga teksturnya menjadi sekeras kayu dan berwarna cokelat tua kehitaman. Biasanya olahan ikan kayu menggunakan ikan cakalang, akan tetapi ikan kayu yang diolah dengan asap menyebabkan kadar benzo(a)piren pada daging ikan kayu tinggi. Pemilihan sampel diambil sebanyak 2 potong produk ikan kayu sampel yang diambil akan diserut kemudian akan diblender dan sampel yang sudah disiapkan akan dilakukan pengujian diantaranya anilisa kadar benzo(a)piren dan kadar air. Metode pengujian benzo(a)piren menggunakan HPLC dan pengujian kadar air menggunakan alat Moisture Determination Balance FD-660, Analisa kadar benzo(a)piren dan kadar air diambil dari data 4 tahun terakhir. data trend pada penelitian yang telah dilakukan kadar benzo(a)piren dan kadar air, pada oven listrik paling tinggi kadar benzo(a)piren ditahun 2022 sebesar 4.52 ppb dan kadar air tertinggi ditahun 2021 sebesar 23.50% sedangkan pengasapan konvensional kadar benzo(a)piren paling tinggi ditahun 2019 sebesar 56.6 ppb dan kadar air tertinggi ditahun 2020 sebesar 19.40%. Pengujian analisa kadar air kadar air pada oven sebesar 22.50% dan pengasapan konvensional sebesar 19.40% Kata Kunci: Ikan Kayu, Benzo(a)piren, Kadar Air, Pengasapan, Oven.